Analisis Keterampilan Teknik Bermain Futsal Pada Pertandingan Final FIFA Word Cup 2021 Antara Argentina VS Portugal - Muhammad Syeikhul Islam Alakbar; Achmad Widodo (Student Research Journal, 2024)
This research aims to analyze the skills of the two teams of futsal players, the Argentine national team and the Portuguese national team in the 2021 FIFA World Cup final match from various aspects including passing, shooting, control and dribbling. The data collection method was carried out through direct tests involving amateur football players competing at the national level. The results of the analysis showed significant variations in physical condition between players. The results of the analysis show significant variations in the skills of both teams of players. The aim of this research is to understand the effectiveness of Argentina and Portugal in the 2021 FIFA World Cup Final match, which ended with a score of 1-2 for Portugal and thus became champions of the championship. The research method used is quantitative descriptive. The data source for this research comes from the video of the 2021 FIFA Wordl Final match. The results of the research in the 2021 Copa America Final match Argentina made 446 (88.14%) accurate passes and 60 (11.86%) inaccurate passes. 19 (54.28%), leading to success as much as 39 (60.93%) and successful control obtained by 378 (95.45%), in conclusion the playing technique used by Argentina should have been superior but was still unable to break into Portugal's goal. Both teams played very well according to the data that had been taken, but there were differences in the formation of the two teams. Portugal was able to withstand attacks prepared by Argentine players and had solid cooperation between the lines. Meanwhile, Argentina should have many attack options but has not been able to score goals and has not been able to solve Portugal's strategy. After analyzing the playing technical performance of the Portuguese National Team, a good conclusion was obtained, but the advantages were not utilized optimally and the opportunities obtained will be used as material for the team's previous evaluation.